The Role of Magnetic Resonance Venography in Headache Due to Suspected Cerebral Venous Sinus Thrombosis in the Presence of Normal T1 and T2 Dural Sinus Signal - Fariha Afzal; Muhammad Imran Khan; Ujala Afridi; Alia Bangash (Gandhara University, 2023)
OBJECTIVES Cerebral venous sinus thrombosis (CVST) is an important but uncommon aetiology of stroke.  The presentation of CVST is extremely variable clinically, moreover its onset can be either acute or subacute, and less frequently, chronic. Headache is the most common symptom of CVST.  The headache is typically diffuse and progressing in severity over days to weeks.  MRI and MRV have very high sensitivity and specificity and have become the modality of choice to confirm the diagnosis of CVST.  The aim of this study was to weigh the benefits of added MRV in patients with headache, after a negative MRI for CVST.  METHODOLOGY The total number of patients included was 207, with chief complaints of headache and suspicion of CVST. The MRV sequence used was dynamic coronal by using the time-of-flight technique. The diagnosis of CVST was made by the loss of normal signal void both on T1WI and T2WI as well as on non-visualization on MRV. RESULTS Out of these 207 patients, CVST was present in 52 patients.  Superior sagittal sinus was involved in 8 cases, right transverse sinus in 2 cases, left transverse sinus in 7 cases, left sigmoid sinus in 3 cases, and multiple sinuses in 32 cases. 34 cases out of 52 had infarction which was mostly haemorrhagic i.e. 27.  A total of 97 cases (46%) had aplastic/hypoplastic transverse segments which were mostly the left one (87, 42%) and 10 cases (4.8 %) on the right side. In none of the patients, CVST was picked by MRV alone after a negative T1 and T2 MRI. CONCLUSION In patients presenting with headache and suspected CVST additional MRV is only required if the routine MR sequences are not able to pick up the thrombus and the suspicion of CVST is very high.